Postawa gracza w zespole wobec obiektywnego prawdopodobien'stwa kontroli antydopingowej - Mroczkowska, H. (Polish Journal of Sport and Tourism, 2010)
The aim of this study was to describe the daring and overcautious attitudes towards doping of team games players in three hypothetical situations differentiated by the objective probability of doping control. Material and methods. A group of volleyball players (n=29), students of the Sports Championship School (SMS), aged about 17 years was examined. An experimental technique, constructed for the purpose of these studies was used to measure: 1. individual hierarchy of values, possible to lose in the consequence of doping use; 2. personally acceptable risk level of impairment in three experimental situations: a) low objective risk (as 2 to 10), b) the average objective risk (such as 5 to 10), c) high objective risk (such as 8 to 10). Results. It has been shown that among the team players, no player has met the criterion of being qualified to the group of daring (the criterion developed in individual sports). Generally, young athletes valued attributes of personal and social integrity significantly higher than the outer functioning attributes. The two most prized values, the loss of which would be the most difficult for the young players to accept, were respectively: the social respect (5.2) and health (4.8). The least appreciated value, whose loss would be easier to reconcile for the young athletes was the financial gratification (2.2) - the difference between these ranks were significant (p < 0.05). In conditions of objective low risk, the overcautious accepted twice less risk than the quasi-daring; in the circumstances of increased risk (at the average level) the overcautious accepted up to 5 times less risk of loss than their peers with the willingness to take risks. Conclusions. Regardless of the individual needs of risking, as the growing threat to lose everything is becoming more important - personally accepted the risk of loss is comparable, regardless of what goods are concerned. This regularity is stronger and more clearly characterizes and polarizes the attitude of the overcautious as compared to the quasi-daring.